Challenges faced by professionals working in child sexual abuse multi-sectorial forums: a case of the Victim-Friendly System in Zimbabwe - Muridzo, Noel G.; Chikadzi, Victor; Kaseke, Edwin (Stellenbosch University, 2020)
This article discusses the challenges faced by role players who work with survivors of child sexual abuse within the Victim-Friendly System. The Victim Friendly System represents a confluence of multi-sectorial professional interventions targeting child sexual abuse survivors in Zimbabwe. Professionals involved in the Victim-Friendly System include social workers, medical doctors, nurses, police, as well as role players within the justice system such as magistrates and prosecutors, counsellors, educationists and psychologists. The findings of this qualitative study show that professionals work within the context of a shrinking economy that has given rise to a plethora of challenges that include, among other things, staff and skills shortages, lack of financial and material resources, poor access to proper infrastructure and other logistical constrains. The authors end the paper by discussing recommendations that have policy, administrative and professional implications